Development Of Google Sites-Based Learning Media To Increase Student Learning Interest - Laili, Ana Mustafidatul; Widarti, Hayuni Retno; Puspita, Ana Pertiwi Indah; Anantayani, Aisyah; Amrullah, Nur Kholish; Aini, Rofinda Gita (IJCER (International Journal of Chemistry Education Research), 2025)
Educational websites utilize information and communication technology to facilitate active learning for students, unrestricted by time and location. As a form of digital media, websites offer numerous benefits, such as the capacity to host extensive materials, making them ideal supplementary resources for students. The flexibility of websites allows for easy access without concerns about time constraints or high costs. One effective platform for creating educational websites is Google Sites, which is user-friendly, efficient in internet data and storage usage, and requires no complex programming skills. Furthermore, Google ensures security for its users and offers free website development. These sites can be designed to feature comprehensive content and visually appealing layouts to boost student engagement. The accessibility and advantages presented by Google Sites address the challenge of low student interest in chemistry, making its development a suitable solution. This research is classified as research and development (R&D), using the ADDIE instructional development model which aims to produce products in the form of google site-based learning media on the material of the mole concept. The study's findings indicated a validation score of 90.26% from subject matter experts, categorized as very feasible/valid, and 89.67% from media experts, also deemed very feasible/valid. Additionally, a readability assessment of the learning website achieved a score of 86.11%, meeting easy-to-understand criteria. The website has been implemented in classroom learning. The results of the analysis of student scores before and after the test showed an increase in learning interest. Although the increase is relatively low, with an N-Gain value of 0.21, these results indicate the potential for further improvement if the research is developed more optimally. Thus, it can be concluded that Google Sites-based learning media on the material of the mole concept has the potential to increase student interest in learning.